KUALITAS PELAYANAN KESEHATAN MASYARAKAT DI PUSKESMAS LOLAK KABUPATEN BOLAANG MONGONGDOW - PANTAS, LISYUNARTI; LENGKONG, FLORENCE DAICY; POMBENGI, JERICHO Danga (Sam Ratulangi University, 2018)
The purpose of this study is to determine the quality of public health services in puskesmas refusemongondow ballang district. Benefit of research, as information material for district government, districtgovernment refuse and society of method used is qualitative method with descriptive approach type andlocation of research at Puskesmas Lolak Mongondow Ballang District. Based on the results research inaccordance with the indicator that have been proposed by Fandy Tjiptono (2000) with the timelines ofservice, courtesy and hospitality when providing services, ease of getting service and consumer comfort butPuskesmas Lolak until now the quality of service is still not running well there is stell which has not beenon time in the health services as well as there is still a lack of hospitality in providing services and not easyto get services and can not provide comfort in public health services because the quality of public healthsevices in Puskesmas Lolang Mongondow Ballang district has not done well. So in the health services inPuskesmas Lolak should be improved so that public health service the Puskesmas Lolak can be effective.Keywords : Quality of health services in the community at puskesmas